University 101 Study, Strategize and Succeed (Open textbook library., 2018)
Welcome to university! Whether this is your first time in post-secondary education, or whether you are returning to studies, you’re arriving with some goals you want to achieve. Perhaps you are taking a focused program to lead you into your desired career. Perhaps you are exploring courses in different areas, providing a foundation for future specialization. Wherever you are in your journey, you find yourself in a learning environment that is different from one you have experienced before. A good foundation for university is learning how to learn. By taking the time to read this book and work through the exercises included, you are investing in the skills that will support you in all of your classes and future learning. Successful students share a set of skills and habits in common. The good news is that these skills are not a secret; anyone can learn the skills that support successful learning. By taking some time to learn proven study strategies, you will be able to reach your learning goals, and avoid the pitfalls that can take you off-track. Who is this book for? This book focuses on the skills you’ll need to be successful in undergraduate courses or other adult education classes. If you are: new to university studies returning to university after some time away a mature student an international student or a continuing student who wants to improve their current skills and strategies this book is meant to support you in your journey.